Effects of mild steel welding fume particles on pulmonary epithelial inflammation and endothelial activation - Samulin Erdem, Johanna (Toxicol Ind Health, 2020)
Welders have an increased risk for cardiovascular disease (CVD) following exposure to welding fumes. The underlying mechanisms are largely unknown; however, oxidative stress, systemic inflammation, and endothelial dysfunction have been suggested as contributing factors to particle-induced CVD. We investigated effects of mild steel welding fume (MSWF) on three target cell types: macrophages, pulmonary epithelial, and vascular endothelial cells. Cells were exposed to MSWF at nontoxic doses for 6 h/day, for five consecutive days. The expression of 40 genes involved in inflammation, fibrosis, and endothelial activation was analyzed. Moreover, changes in the reactive oxygen species production and migration capacity of cells were assessed. The expression of matrix metallopeptidase 1 (MMP1) was induced in both epithelial and endothelial cells following repeated exposure to MSWF. Although MMP1 is important in inflammatory responses in vivo, this effect was not concurrent with changes in the inflammatory status, cell proliferation, and migration capacities, nor did it induce oxidative stress in the cells. Thus, repeated exposure with low doses of MSWF was sufficient neither for inducing inflammatory stress in epithelial cells and macrophages nor for endothelial activation, and higher concentrations of MSWF or the nonparticle fraction of MSWF may be critical in causing the increased risk of CVD observed among welders.